Cardioprotective effect of MMP‐2‐inhibitor‐NO‐donor hybrid against ischaemia/reperfusion injury. Issue 4 (7th February 2019) - Krzywonos‐Zawadzka, Anna; Franczak, Aleksandra; Olejnik, Agnieszka; Radomski, Marek; Gilmer, John F.; Sawicki, Grzegorz; Woźniak, Mieczysław; Bil‐Lula, Iwona
Abstract: Hypoxic injury of cardiovascular system is one of the most frequent complications following ischaemia. Heart injury arises from increased degradation of contractile proteins, such as myosin light chains (MLCs) and troponin I by matrix metalloproteinase 2 (MMP‐2). The aim of the current research was to study the effects of 5‐phenyloxyphenyl‐5‐aminoalkyl nitrate barbiturate (MMP‐2‐inhibitor‐NO‐donor hybrid) on hearts subjected to ischaemia/reperfusion (I/R) injury. Primary human cardiac myocytes and Wistar rat hearts perfused using Langendorff method have been used. Human cardiomyocytes or rat hearts were subjected to I/R in the presence or absence of tested hybrid. Haemodynamic parameters of heart function, markers of I/R injury, gene and protein expression of MMP‐2, MMP‐9, inducible form of NOS (iNOS), asymmetric dimethylarginine (ADMA), as well as MMP‐2 activity were measured. Mechanical heart function, coronary flow (CF) and heart rate (HR) were decreased in hearts subjected to I/R Treatment of hearts with the hybrid (1‐10 µmol/L) resulted in a concentration‐dependent recovery of mechanical function, improved CF and HR. This improvement was associated with decreased tissue injury and reduction of synthesis and activity of MMP‐2. Decreased activity of intracellular MMP‐2 led to reduced degradation of MLC and improved myocyte contractility in a concentration‐dependent manner. An infusion of a MMP‐2‐inhibitor‐NO‐donor hybrid into I/R hearts decreased the expression of iNOS and reduced the levels of ADMA. Thus, 5‐phenyloxyphenyl‐5‐aminoalkyl nitrate barbiturate protects heart from I/R injury.